Bacterial fatty acids enhance recovery from the dauer larva in Caenorhabditis elegans. - Tiffany K Kaul (Public Library of Science (PLoS), 2014)
The dauer larva is a specialized dispersal stage in the nematode Caenorhabditis elegans that allows the animal to survive starvation for an extended period of time. The dauer does not feed, but uses chemosensation to identify new food sources and to determine whether to resume reproductive growth. Bacteria produce food signals that promote recovery of the dauer larva, but the chemical identities of these signals remain poorly defined. We find that bacterial fatty acids in the environment augment recovery from the dauer stage under permissive conditions. The effect of increased fatty acids on different dauer constitutive mutants indicates a role for insulin peptide secretion in coordinating recovery from the dauer stage in response to fatty acids. These data suggest that worms can sense the presence of fatty acids in the environment and that elevated levels can promote recovery from dauer arrest. This may be important in the natural environment where the dauer larva needs to determine whether the environment is appropriate to support reproductive growth following dauer exit.